Analisis Relevansi Visi, Misi, Tujuan, dan Kurikulum Antara SMKN 1 Kedawung Sragen dan SMKN 1 Bawen Semarang - Fadillah Windaningrum (IAIN PAREPARE, 2019)
The school is an educational institution that has a vision, mission, goals, and curriculum as the identity and personality of the school. This study aims to understand the substance of the vision, mission, goals, and curriculum of the two schools, and to determine the suitability of the vision and mission goals as well as the curriculum applied in both agriculture-based vocational schools. This research method is descriptive-comparative which is qualitative. The data analysis technique used is constant comparative, which is the stage of comparing events that can be applied to each category, the stage of integrating categories and their characteristics, the stage of limiting the scope of the theory, and the stage of writing the theory. The results of the study showed the appropriateness of the vision, mission, goals, and curriculum that became the ideals or dreams achieved in the future by SMK N 1 Kedawung Sragen and SMK N 1 Bawen Semarang